Um mecanismo de melhoria de handovers verticais utilizando endereçamento multicast e serviços do MIH 802.21 - Bonfim, Michel Sales (2011)
The use of multi-interface devices such as smart phones has grown at the same time as the demands for efficient mobility services in heterogeneous networks. In this scenario, the idea of service continuity has become a crucial requirement. To achieve these demands, efficient handover schemes should be developed aiming to achieve Seamless Handover, which means the change of network domains in a transparent way and without services discontinuity to the end user. Currently, there are different schemes for handover and some of them may be used between different access technologies (Vertical Handover). However, the service time disruption is still a major problem to be solved. The main purpose of this study is to propose an improvement for Vertical Handovers using IP mobility, aiming at Seamless Handover. In this work, the framework provided by the MIH (Media Independent Handover) IEEE 802.21 is used to enable vertical handover in heterogeneous networks, and propose an extension of FMIPv6 (Fast Handovers for Mobile IPv6) called FaHMA (Fast Handovers using Multicast Addressing), using multicast in order to manage mobility in these types of networks. To make the performance analysis, we decided for simulations and we considerered metrics such as the handover delay and packet loss as the most important criteria for evaluating the effectiveness of our proposal. Simulation results have shown that FaHMA achieve better results than FMIPv6, including factors that determine the quality of operation in networked multimedia applications.